A low-molecular-weight dialysable leukocyte extract selectively enhances development of CD4⁺RORγt⁺ T cells and IL-17 production - Zajícová, A; Javorková, E; Trošan, P; Chudíčková, M; Krulová, M; Holáň, V (Folia biologica, 2014)
A low-molecular-weight (under 10 kDa) dialysable leukocyte extract (called transfer factor, TF) has been shown to be a prospective substance to improve or modulate immune response in autoimmunity, inflammation, infectious diseases or cancers. However, the use of TF has been limited by the absence of any data on the mechanism of its action. Here we show that TF prepared from peripheral blood leukocytes of healthy human donors displays multiple regulatory effects on individual parameters of the immune system. TF decreases proliferation of T and B lymphocytes and partially alters the production of cytokines and nitric oxide by activated macrophages. TF also inhibits production of T helper 1 (Th1) cytokines interleukin 2 (IL-2) and interferon γ, slightly stimulates production of Th2 cytokine IL-10 and considerably enhances the secretion of IL-17 by activated mouse spleen T cells. At the molecular level, TF enhances expression of genes for transcription factor RORγt and for IL-17. The enhanced expression of the RORgt gene corresponds with an increase in the number of RORγt⁺CD4⁺ Th17 cells and with enhanced IL-17 production. In contrast, the expression of the Foxp3 gene and the proportion of CD4⁺CD25⁺Foxp3⁺ regulatory T cells are not significantly changed in the presence of TF. These results suggest that the activation of pro-inflammatory Th17 cells, which have multiple immunoregulatory properties, could be the main mechanism of the immunomodulatory action of a low-molecular-weight leukocyte extract.
Keywords: Forkhead Transcription Factors; interleukin-17; peritoneální makrofágy; Cell Division; Drug Evaluation, Preclinical; preklinické hodnocení léčiv; Adjuvants, Immunologic; regulace genové exprese; molekulová hmotnost; forkhead transkripční faktory; adjuvancia imunologická; podskupiny lymfocytů; oxid dusnatý; Interleukin-17; Molecular Weight; myši inbrední BALB C; zvířata; Nitric Oxide; myši; Cells, Cultured; Lymphocyte Activation; Macrophages, Peritoneal; B-lymfocyty; Mice; aktivace lymfocytů; Lymphocyte Subsets; Gene Expression Regulation; CD4-Positive T-Lymphocytes; Concanavalin A; Nuclear Receptor Subfamily 1, Group F, Member 3; interleukiny; kultivované buňky; B-Lymphocytes; Spleen; Transfer Factor; CD4-pozitivní T-lymfocyty; Real-Time Polymerase Chain Reaction; interferon gama; jaderné receptory - podrodina 1, skupina F, člen 3; Interleukins; Animals; transfer faktor; konkanavalin A; kvantitativní polymerázová řetězová reakce; Mice, Inbred BALB C; Interferon-gamma; slezina; buněčné dělení